2019
DOI: 10.3390/md17060349
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Containing Carotenoids from A Marine Coral Symbiont Erythrobacter flavus Strain KJ5

Abstract: Erythrobacter flavus strain KJ5 (formerly called Erythrobacter sp. strain KJ5) is a yellowish marine bacterium that was isolated from a hard coral Acropora nasuta in the Karimunjawa Islands, Indonesia. The complete genome sequence of the bacterium has been reported recently. In this study, we examined the carotenoid composition of this bacterium using high-performance liquid chromatography coupled with ESI-MS/MS. We found that the bacterium produced sulfur-containing carotenoids, i.e., caloxanthin sulfate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Erythrobacter, Winogradskyella, Phaeodactylibacter, Muricauda, and unresolved Rhodobacteraceae genera were significantly more abundant in control anemones compared to "sterile" anemones. At least three of these groups (Erythrobacter, Winogradskyella, and Muricauda) are common members of the Symbiodiniaceae microbiome (Lawson et al, 2017;Nitschke et al, 2020) and some are known carotenoid producers (Prabhu et al, 2014;Zhang et al, 2016;Setiyono et al, 2019), which could serve as potent antioxidants protecting the algal symbiont during periods of oxidative stress (Schmitt et al, 2014). Erythrobacter produces enzymes that can inactivate common antibacterial compounds (Jiang et al, 2018), while Winogradskyella produces antifouling compounds (Dash et al, 2009).…”
Section: Potential Key Microbiome Members Of Exaiptasiamentioning
confidence: 99%
“…Erythrobacter, Winogradskyella, Phaeodactylibacter, Muricauda, and unresolved Rhodobacteraceae genera were significantly more abundant in control anemones compared to "sterile" anemones. At least three of these groups (Erythrobacter, Winogradskyella, and Muricauda) are common members of the Symbiodiniaceae microbiome (Lawson et al, 2017;Nitschke et al, 2020) and some are known carotenoid producers (Prabhu et al, 2014;Zhang et al, 2016;Setiyono et al, 2019), which could serve as potent antioxidants protecting the algal symbiont during periods of oxidative stress (Schmitt et al, 2014). Erythrobacter produces enzymes that can inactivate common antibacterial compounds (Jiang et al, 2018), while Winogradskyella produces antifouling compounds (Dash et al, 2009).…”
Section: Potential Key Microbiome Members Of Exaiptasiamentioning
confidence: 99%
“…strain KJ5) is a yellowish aerobic marine bacterium, which was isolated from the hard coral Acropora nasuta (family: Acroporidae) in the Karimunjawa Islands, Central Java Province, Indonesia. It is worth to mention that previous phylogenetic analysis utilizing 16S rDNA sequence had shown that this species has a genetic similarity of 96% to E. flavus [ 41 ]. The genus Erythrobacter was first classified by Shiba and Simidu [ 42 ], and found to compromise aerobic marine photosynthetic bacteria that have bacteriochlorophyll, carotenoids as well as non-sulphated carotenoids.…”
Section: Scleractinia-associated Bacteriamentioning
confidence: 99%
“…For example, Setiyono et al . (2019) first reported the compound zeaxanthin sulphate, a carotenoid produced by Erythrobacter flavus KJ5 from the stony coral A. nasuta in Indonesia. This bacterium also produced other known sulphur carotenoids, caloxanthin and nostoxanthin sulphate (Setiyono et al .…”
Section: Secondary Metabolites From Cabmentioning
confidence: 99%
“…This bacterium also produced other known sulphur carotenoids, caloxanthin and nostoxanthin sulphate (Setiyono et al . 2019). Carotenoids are widely used in food, cosmetic and pharmaceutical industries (Galasso et al .…”
Section: Secondary Metabolites From Cabmentioning
confidence: 99%